Bookkeeping information use for implementing management principles - BĂLUŢĂ, Aurelian Virgil (Annals of Spiru Haret University. Economic Series, 2010)
One of the principles used for the new projects and agreed by the enterprisers is that of 3D. In order to apply this principle, one needs to use bookkeeping information. In the attempt of managers to be successful in business, there is also used the bookkeeping information. The managers use a series of practices in order to increase the companies’ performance. For most cases, the account department helps the successful managerial practices with adequate information and procedures.